2007
DOI: 10.1002/gcc.20514
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of PRKCI, located in 3q26, is associated with lymph node metastasis in esophageal squamous cell carcinoma

Abstract: DNA amplification is one of the mechanisms to activate genes that are implicated in neoplastic transformation and gain of chromosome band 3q26 is a common event in squamous cell carcinomas. The aim of the present work was to identify the specific target gene from four candidates (MDS1, PRKCI, ECT2, and PIK3CA) located on 3q26 amplification in esophageal squamous cell carcinomas (ESCCs). To assess the prevalence of copy number gains of putative genes, fluorescence in situ hybridization (FISH) was applied on 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 37 publications
5
67
0
Order By: Relevance
“…10,11 Importantly, the PKCl/i gene is located at the 3q26.2 genomic region, which is most frequently amplified in human cancer 16,17 , and overexpression of PKCl/i has been implicated in cancer development in multiple tissues including the lung, 18,19 pancreas, 20 stomach, 21 colon, 22 esophagus, 23 liver, 24 bile duct, 25 ovary, 17 prostate 26 and brain. 27 Recently, few studies have been reported higher expression of PKCl/i in ER/PRand HER-positive breast cancer and also in lymph node metastases.…”
mentioning
confidence: 99%
“…10,11 Importantly, the PKCl/i gene is located at the 3q26.2 genomic region, which is most frequently amplified in human cancer 16,17 , and overexpression of PKCl/i has been implicated in cancer development in multiple tissues including the lung, 18,19 pancreas, 20 stomach, 21 colon, 22 esophagus, 23 liver, 24 bile duct, 25 ovary, 17 prostate 26 and brain. 27 Recently, few studies have been reported higher expression of PKCl/i in ER/PRand HER-positive breast cancer and also in lymph node metastases.…”
mentioning
confidence: 99%
“…In addition, PKR-like endoplasmic reticulum kinase has a role in limiting oxidative damage (Bobrovnikova-Marjon et al 2010). PKCι is an oncoprotein in esophageal squamous cell carcinoma (Yang et al 2008), and one of its roles is to promote cancer cell metastasis (Liu et al 2011). The present work demonstrated an additional role for this oncoprotein in counteracting oxidative stress-induced apoptosis in esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical protein kinase Cι (PKCι) has been identified as an oncoprotein in lung cancer (Regala et al 2005a, b), ovarian cancer (Eder et al 2005), gastric cancer (Takagawa et al 2010), colon cancer (Murray et al 2004), and esophageal squamous cell carcinoma (ESCC) (Yang et al 2008). PKCι regulates multiple malignant phenotypes and several oncogenic signaling pathways in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The PKCι gene is amplified as part of the 3q26 amplicon in lung (Regala et al, 2005b), esophageal (Yang et al, 2008) and ovarian (Eder et al, 2005;Zhang et al, 2006) cancers. A P118L mutation was found in a metastatic melanoma sample (Greenman et al, 2007).…”
Section: Somaticmentioning
confidence: 99%
“…Note PKCι overexpression has been observed in numerous human cancers including cancers of the lung (Regala et al, 2005b), pancreas (Scotti et al, 2010), stomach (Takagawa et al, 2010), colon (Murray et al, 2004), esophagus (Yang et al, 2008), liver (Du et al, 2009), bile duct (Li et al, 2008), breast (Kojima et al, 2008), ovary (Weichert et al, 2003;Eder et al, 2005;Zhang et al, 2006), prostate (Ishiguro et al, 2009), and brain (Patel et al, 2008). PKCι is itself an oncogene, which appears to be activated through tumor-specific overexpression.…”
Section: Various Cancersmentioning
confidence: 99%